2009
DOI: 10.1051/alr/2009009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of trout aquaculture on water quality and farm effluent treatment options

Abstract: -In the context of the European Water Framework Directive, the in-and outflow water quality from 13 German trout farms, rearing mainly rainbow trout (Oncorhynchus mykiss) and using inflow rates between 0.03-0.80 m 3 s −1 , were monitored for point-source pollution. The farms had a significant effect on the effluent quality and macro-invertebrate fauna in adjacent streams (saprobic index based on species assemblage and abundance was 1.56-2.10 upstream of the farms but increased to 2.06-2.37 downstream of the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
3
15
0
2
Order By: Relevance
“…In this study, eight parameters were used to calculate WQI min considering that these variables have impacts on the water quality (Bergheim and Brinker, 2003;Sindilariu et al, 2009a;Koc¸er et al, 2013). The WQI min in this way yielded high score (69.07) compared to the WQI obj (63.80).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, eight parameters were used to calculate WQI min considering that these variables have impacts on the water quality (Bergheim and Brinker, 2003;Sindilariu et al, 2009a;Koc¸er et al, 2013). The WQI min in this way yielded high score (69.07) compared to the WQI obj (63.80).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the movements of the prawns on the bottom of the ponds contributes to the resuspension into the water column of detritus (e.g., feed, dead plankton, clay), which contains N and P in its constitution (Hargreaves, 1998). Many studies have shown that aquaculture causes impacts on water from the addition of nutrients (CasillasHernández et al, 2006;Henry-Silva and Camargo, 2006;Sindilaru et al, 2009;Anh et al, 2010). However, it is not easy to quantitatively compare the results of these studies and to indicate how the species cultivated or the management techniques used add more nutrients to the pond water.…”
Section: Variablesmentioning
confidence: 99%
“…For farms that are located in areas where a large quantity of low cost land is available, halophyte constructed wetlands (CWs) provide an IMTA approach that is cost-effective, requires moderate capital investment, and has low energy consumption and maintenance expenses [210][211][212].…”
Section: Discussionmentioning
confidence: 99%
“…Providing inexpensive land is available, the integration of CWs into on-land aquaculture can be very cost-effective as they only require moderate capital investment and have low energy consumption and maintenance expenses [210][211][212]. However, CWs require relatively extensive areas of land, and would not be suitable in locations where land prices are high.…”
Section: Halophyte Wetlands (On-land)mentioning
confidence: 99%